Informative report of immigration and job opportunities - Friesen, Abigail (Kansas State University. K-State Libraries, 2014)
In this informative report, I have written a mock memo to the United States Secretary of Labor informing him of the immigration policies and laws in place that target Latin Americans. By doing this, my goal was to raise awareness of the racial inequality the immigration laws and policies were centered on in the mind of the United States Secretary of Labor, in the hopes that this awareness might lead to change. First, I found policies that restricted the number of visas and citizenships granted by the United States to Latin American countries. Next, I explored the policies that restrict the hiring of Latin Americans, once again discriminating their employment freedom in the United States. Finally, the last set of policies I looked into were those that Latin American business owners must follow to run a business and hire employees. The policies discussed in this paper were brought to the attention of the Secretary of Labor in the hopes that a change in the policies and the policy making within the government's departments might lead to an equality for all people in the job industry.
Citation: Friesen, A. (2014). Informative report of immigration and job opportunities. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Individual Freshman category, honorable mention
Keywords: Immigration; Jobs; Race; Hardships; Latin Americans